(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
With more than 250 ethnic groups and more than 500 indigenous languages, Nigeria’s educational system functions in a very multicultural and multilingual environment. For the advancement of education, this diversity offers both possibilities and difficulties. In addition to preparing students for engagement in a globalized world, cultural diversity and language instruction are essential for promoting inclusivity, social cohesiveness, and national identity. This article explored the relevance of cultural diversity and language instruction in Nigeria’s educational system. It also examined the historical influence of culture on educational policies, benefits of integrating cultural diversity, importance of language education as well as strategies for effective investment in language education. The study maintained that Language instruction and cultural diversity are essential to Nigeria’s educational system’s efficacy and inclusivity. Thus, the study makes the case for resource investment in indigenous language education, strong teacher preparation for multilingual and multicultural pedagogy, and curriculum reforms that take cultural plurality into account. In conclusion, it is imperative that Nigeria’s educational system improve its language instruction and cultural diversity which offers a way to create a society that is more sustainable, cohesive, and inclusive, where education acts as a unifying factor and an instrument for empowerment.